Pruritus, Allergy and Autoimmunity: Paving the Way for an Integrated Understanding of Psychodermatological Diseases? - Ferreira, Bárbara Roque; Pio-Abreu, José Luís; Figueiredo, Américo; Misery, Laurent (Frontiers in Allergy, 2021)
Pruritus is a key symptom in allergology and dermatology, contributing to the global and huge impact on quality of life related to skin disorders, both those which are not related to a primary dermatosis (illness) and those which are linked with primary skin lesions (disease). This is particularly evident within psychophysiological dermatoses, a group of psychodermatological diseases where there is a primary dermatosis, where psychological stress plays a role, and where pruritus may represent a major and shared symptom. The etiopathogenesis of pruritus in those disorders sheds light on the link among psychopathological features, psychological stress and the subtle interface between allergic and autoimmune mechanisms, where mast cells play a pivotal role. Allergy has long been recognised as an altered reactivity to exogenous antigens (allergens), defined as an immediate hypersensitivity mediated by immunoglobulin E (IgE). In turn, the immunological understanding of atopy is related to an immediate hypersensitivity reaction to environmental antigens involving T-helper 2 (Th2) responses and the IgE production. Mast cells are major cells in the early phase of allergy, releasing the mediators involved in the symptoms associated with the allergic disease, including pruritus, when the allergen cross-links with IgE, whose mechanisms can be observed in acute urticaria and atopy. Some allergic reactions may persist and allergy may eventually lead to autoimmunity, with the development of a T-helper 1 (Th1) and then IgE-independent inflammation. For instance, in chronic spontaneous urticaria, the mast cell activation may include autoimmune mechanisms, where autoantibodies against the extracellular α subunit of the high-affinity IgE receptor (FcεRIα) and to IgE are observed, with the involvement of Th1 lymphocytes and the production of interferon-γ (INF-γ). The role of autoimmunity is also suggested in the etiopathogenesis of other psychophysiological dermatoses, namely psoriasis, atopic dermatitis and alopecia areata. In the latter, for example, mast cells were reported to be linked with the loss of immune privilege and they are the key cells involved in the experience of pruritus, whose intensity was reported to precede and be correlated with the onset of the hair loss. Furthermore, considering that the role of hair and skin is wide, from psychosocial aspects (communication and social interaction) to vital functions (such as, temperature control), it is straightforward that they are central in our interactions and synchronization with others and the world; thereby, we may admit that the psychophysiological dermatoses could represent a loss of such synchronization. Furthermore, they are often linked with psychopathology which strongly connects with the concept of desynchronization, namely, sleep disorders and depressive symptoms, the clinical expression of a dysfunction in the interplay among mast cells, pineal gland and melatonin, thus the circadian rhythm, as well as their connection with the hypothalamic corticotrophin-releasing hormone (CRH), well-known for its key role in stress response. Moreover, increasing evidence has supported the existence of cutaneous equivalents for these mechanisms, connecting with those central pathways. Thereby, taking all these concepts into consideration, this review intends to look into the updated evidence on the shared biological mechanisms between allergy and autoimmunity, underlining pruritus as a core element, then revisiting the key role of mast cells and discussing the connection with melatonin and immune-inflammatory pathways in the physiopathology of psychophysiological dermatoses, thus paving the way for the understanding of their psychosomatic correlates and a comprehensive psychodermatological approach.